CGIAR Portfolio 2017-2022 - Kropff, Martin (Wageningen University & Research, 2016)
Presentation of the CGIAR Portfolio 2017-2022 to the CGIAR System Council by Martin Kropff, the Interim System Management Board Chair, September 2016.